Research on the Green Technology Innovation Cultivation Path of Manufacturing Enterprises Under the Regulation of Environmental Protection Tax Law in China - Chen, Yongqing; Zhang, Tongjian; Ostic, Dragana (Frontiers in Environmental Science, 2022)
In the context of China’s path to industrialization advancement, environmental problems are becoming increasingly serious. Therefore, the cultivation of green technology innovation has become an urgent task during the current industrialization development. According to the “Porter hypothesis,” environmental regulation is an important driving force for green technology innovation. Environmental tax is a typical environmental regulation, although it was implemented late in China. Green technology innovation is one of the long-term effects of environmental tax collection. Using multiple regression analysis and taking Chinese manufacturing enterprises as samples, this study constructs and tests a model of environmental tax promotion and its effect on green technology innovation, revealing the micro-mechanism of environmental tax incentives and also finding that sufficient environmental tax incentives are lacking. The strategy of green technology innovation cultivation for manufacturing enterprises in China under the current environmental tax regulation is provided in this article in order to provide a current theoretical reference point for the development of China’s ecological economy.